FIX&FOXY’s Poetics, Method and Organisation: Interview with Tue Biering, October 2021 and January 2022 - Exe Christoffersen, Erik; Krøgholt, Ida; Winkelhorn, Kathrine (Peripeti, 2023)
Interview with Biering by Christoffersen, Krøgholt and Winkelhorn. Biering tells about the principles and the theatre view that have been guiding for FIX&FOXY’s creative and theatrical strategies throughout the theatre’s work.